Microbiological profile of leg ulcer infections: review study - Taysa de Fátima Garcia; Eline Lima Borges; Thaisa Oliveira de Castro Junho; Josimare Aparecida Otoni Spira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the microbiological profile of leg ulcers of patients treated at outpatient clinics and hospitals regarding the type of microorganism, microbiological selection of antibiotics, and techniques for the collection of culture material. Methods: literature review performed on LILACS, IBECS, MEDLINE, and CINAHL databases, resulting in a descriptive analysis of 27 studies. Results: 35.7% of the studies occurred in an outpatient care scenario; and 64.2% in hospitals. There was a predominance of swab (100%) in outpatient care and biopsy (55.5%) in the hospital. Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus were more common at both levels of assistance. Methicillin-resistant Staphylococcus aureus was isolated in both. Conclusions: the microbiological profile of infections was similar, with the presence of resistant bacteria in both environments. This fact causes concern and raises the need for research to elucidate it. The studies did not compare the effectiveness between biopsy and swab.